Pengaruh model role playing terhadap kemampuan berpikir kreatif siswa pada mata pelakaran IPAS di kelas IV Sekolah Dasar - Apriyanti, Chika; Nuraeni, Fitri; Caturiasari, Jennyta (Jurnal Pendidikan Dasar, 2024)
The ability to think creatively is one of the abilities that needs to be improved in 21st century learning. However, in reality elementary school students' creative thinking is still low, including in Natural and Social Sciences lessons, Social Sciences sub-material. This is because the learning model used to teach social studies material is still monotonous and lecture-based. Based on this, the aim of this research is to determine the effect of role playing models on improving students' creative thinking abilities in Natural and Social Sciences subjects, Social Sciences sub-material. The type of research used in this research is a quasi-experimental model with a non-equivalent control group design, namely conducting a pretest and posttest in the experimental class and control class. The subjects in this research were 52 students of class IV elementary school consisting of 26 students of class IV A and 26 students of class IV B. The results of this research concluded that the increase in creative thinking abilities of students who received learning using the role playing model was better than that of students who receive conventional learning and there is an influence of the role playing model of 51% on students' creative thinking abilities in terms of the results of simple linear regression analysis.